The flywheel leg-curl machine: Offering eccentric overload for hamstring development - Tous-Fajardo, J.; Maldonado, R. A.; Quintana, J. M.; Pozzo, M.; Tesch, P. A. (International Journal of Sports Physiology and Performance, 2006)
For the sole purpose of developing knee-fl exor strength, power, and size, almost any weight room or training facility is equipped with a prone, face-down leg-curl weight-stack machine. Such commercially available machines all aim at targeting and isolating the knee-flexor muscle group. Depending on mechanical design, they differ somewhat with regard to external torque offered and hence muscle use in the desired range of motion. Given the high rate of injury reported for the flexormuscle group in athletes relying on high horizontal speed and power and the fact that leg-curl machines are frequently used both in prevention and rehabilitation of hamstring injuries, the scant information describing the basic kinematics of this exercise is rather surprising. A novel leg-curl device (YoYo™ Technology AB, Stockholm, Sweden) uses the inertia offered by rotating flywheels to provide resistance. Contrary to traditional weight-stack machines, this loading feature allows for exercise with eccentric overload, as shown elsewhere for configurations aimed at other muscle groups.With use of the flywheel leg curl, an 8-week training program improved maximal running speed and, perhaps even more important, reduced the incidence of hamstring strains in elite soccer players. Unfortunately, force-velocity profiles and electromyographic (EMG) activity during concentric-eccentric actions on this device were never examined. Here, we report kinematic data in athletes performing all-out knee flexions at different inertial settings using this particular flywheel configuration.